2021
DOI: 10.1182/blood-2021-146907
|View full text |Cite
|
Sign up to set email alerts
|

Pomalidomide and Dexamethasone with or without Subcutaneous Daratumumab in Patients with Relapsed or Refractory Multiple Myeloma: Updated Analysis of the Phase 3 Apollo Study

Abstract: Introduction: Daratumumab (DARA) is a human IgGκ monoclonal antibody targeting CD38 with a direct on-tumor and immunomodulatory mechanism of action. DARA is approved as monotherapy or in combination with standard-of-care regimens for the treatment of relapsed or refractory multiple myeloma (RRMM). In the primary analysis (median follow-up, 16.9 months) of the phase 3 APOLLO study (NCT03180736), the addition of DARA to pomalidomide and dexamethasone (D-Pd) showed a significant progression-free survival (PFS) im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In the PERSEUS study, the 48-month PFS rate was 84.3% in the D-RVd arm and 67.7% in the RVd arm (HR 0.42; 95% CI 0.30-0.59, p <0.001), and in the GRIFFIN trial, the 4-year PFS was 87% in the D-RVd arm and 70% in the RVd arm (HR 0.45, 95% CI 0.23-0.95). [5,6] In our analysis, the results were quite similar with what was seen in the phase 2 and 3 setting with an estimated 4-year PFS rate of 85% in the D-RVd arm and 61% in the RVd arm. This consistency provides further confidence in the validity of our data.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the PERSEUS study, the 48-month PFS rate was 84.3% in the D-RVd arm and 67.7% in the RVd arm (HR 0.42; 95% CI 0.30-0.59, p <0.001), and in the GRIFFIN trial, the 4-year PFS was 87% in the D-RVd arm and 70% in the RVd arm (HR 0.45, 95% CI 0.23-0.95). [5,6] In our analysis, the results were quite similar with what was seen in the phase 2 and 3 setting with an estimated 4-year PFS rate of 85% in the D-RVd arm and 61% in the RVd arm. This consistency provides further confidence in the validity of our data.…”
Section: Discussionsupporting
confidence: 83%
“…In sum, this randomized data is quite convincing and supports quadruplet induction therapy as the new standard of care. [6] Recognizing the potential benefit of daratumumab in induction, we modified our standard of care treatment to Dara-RVd for NDMM patients at our institution in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The phase II GRIFFIN trial tested Dara-VRd as induction with AHCT and showed similarly excellent 2-year PFS at 95.8% (68). The recently published phase III PERSEUS trial compared Dara-VRd vs VRd in induction and post-AHCT consolidation, and demonstrated a significant improvement in PFS with the addition of Dara (84.3% 4-year PFS, vs 67.7% in the VRd only group) (6). Importantly PERSEUS reported a powerful depth of response with 75.2% of patients in the D-VRd group achieving MRD-negativity.…”
Section: Autologous Hematopoietic Stem Cell Transplantmentioning
confidence: 99%
“…For 2023, an estimated 35,730 new cases will be diagnosed in the United States which represents 1.8% of all cancers and 19% of all hematologic malignancies (1). The advent of high doses of melphalan with autologous hematopoietic stem cell transplantation (AHCT) was a major advance and led to improved response rates (RR), progression free survival (PFS), and, in some trials, prolonged overall survival (OS) in patients with newly diagnosed MM (NDMM) and has been a cornerstone of treatment in eligible patients for the last 20 years (2)(3)(4)(5)(6). While there are no universally agreed upon transplant eligibility criteria and several risk stratification tools have been proposed, factors such as age, baseline performance status, and comorbidities are important tenets in determining a patient's eligibility (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%